RETINOPATHY OF PREMATURE INFANTS AS A MAIN PROBLEM OF NEONATAL OPHTHALMOLOGY - P. V. Rozental’ (Вопросы современной педиатрии, 2014)
During more than 70 years retinopathy of premature infants (previously — retrolental retinopathy) has been one of the main problems in neonatology practice. This is caused firstly by the high risk of blindness development and visual disability and secondly — by the steady increase of health care allowing infants previously believed to be incurable to survive. Success in prevention of development of severe forms of this disorder nowadays depends not only on knowledge and experience of pediatric ophthalmologists. To the great extent it is associated to efforts and awareness of all levels of medical care participating in management of premature infants: from maternity hospitals, including departments of intensity care and neonatology, to out-patients clinics. According to the review of modern literature the article contains the main data on etiology, risk factors, pathogenesis, classification, clinical manifestation, diagnostics, prophylaxis and treatment of retinopathy of premature infants. The author also noted the tendencies to reveal the disease in the modern history of the Russian Federation. It is important to say, that urgency of this problem in the Russian Federation has significantly raised during the last years due to switch since the 1st January 2012 to the live birth criteria recommended by the World Health Organization.